Analysis of Water Quality in the Aik Nyet Natural Tourist Attraction, Buwun Sejati Village, West Lombok Regency - Saputra, Haris; Anwar, Hairil; Rini, Dwi Sukma (Jurnal Multidisiplin Madani, 2024)
Water quality is a condition that indicates the quality of water in a body of water, water sources and river basins. Water quality requires testing and analysis by considering its physical conditions, chemical content, and biology. Aik Nyet natural tourist attraction is one of the famous water sources in the Lombok area, West Nusa Tenggara. Bathing and swimming activities in this area can potentially cause pollution of water quality, but until now there has been no information regarding the quality of water in this natural tourist attraction. Therefore, this study aims to analyze the quality of water in the Aik Nyet Natural Tourist Attraction, Sesaot Resort, KPHL Rinjani Barat, Lombok. Water quality is assessed using Class Two water quality standards in accordance with the Decree of the Minister of Environment No. 115 of 2003, alongside identification using the US Environmental Protection Agency (US-EPA) system. Sampling was performed at three distinct points to analyze physical, chemical, and biological parameters. The results of the analysis showed that several parameters such as temperature, pH, ammonia levels, and the number of E. coli bacteria met the quality standards, while the chemical parameters DO and BOD showed mild pollution